TRANSPARENCY, ACCOUNTABILITY, AND AUDIT FINDINGS IN BPK RI TO MINIMIZING THE LEVEL OF CORRUPTION - Nafisah, Salwa; Triyanto, Dedik Nur (Fakultas Bisnis Universitas Katolik Widya Mandala Surabaya, 2019)
According to the data from KPK in 2017, the Ministry and Local Government of Indonesia were laced in the 5th rank of biggest number of corruption case in 2017. This study aims to determine the effect of transparency, accountability, and BPK-RI’s audit findings in minimalize the level of corruption both partially and simultaneously. The population of this study was the Ministry and Local Government of Indonesia in 2017. Samples were determined by using purposive sampling analysis which obtained 24 samples data in total. The data analyzed used in this study were descriptive analysis and multiple linear regression. The result of this study showed that transparency, accountability, and BPK RI’s audit finding have effect in minimalizing the corruption level.